2018
DOI: 10.1038/s41388-017-0037-7
|View full text |Cite
|
Sign up to set email alerts
|

Conditional knockout of N-Myc and STAT interactor disrupts normal mammary development and enhances metastatic ability of mammary tumors

Abstract: The process of organ development requires a delicate balance between cellular plasticity and differentiation. This balance is disrupted in cancer initiation and progression. N-Myc and STAT interactor (NMI: human or Nmi: murine) has emerged as a relevant player in the etiology of breast cancer. However, a fundamental understanding of its relevance to normal mammary biology is lacking. To gain insight into its normal function in mammary gland, we generated a mammary-specific Nmi knockout mouse model. We observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Hypoxia is one of the well-established drivers of epithelial-mesenchymal-transition (EMT). Multiple studies from our group have highlighted the importance of NMI (N-Myc and STAT interactor) protein in negatively impacting EMT ( Devine et al., 2014 ; Pruitt et al., 2018 ). NMI protein contains a previously uncharacterized RNA recognition motif (RRM) at aa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia is one of the well-established drivers of epithelial-mesenchymal-transition (EMT). Multiple studies from our group have highlighted the importance of NMI (N-Myc and STAT interactor) protein in negatively impacting EMT ( Devine et al., 2014 ; Pruitt et al., 2018 ). NMI protein contains a previously uncharacterized RNA recognition motif (RRM) at aa.…”
Section: Resultsmentioning
confidence: 99%
“…Even though there is an absence of studies detailing effects of hypoxia on ribosome biogenesis, multiple studies have defined roles for hypoxia in regulating a program of epithelial-mesenchymal-plasticity ( Prakash et al., 2019 ; Williams et al., 2019 ). Studies from our lab have previously defined a critical role of NMI in tumor progression and metastasis via alterations in the EMT program ( Devine et al., 2014 ; Pruitt et al., 2018 ). Based on these studies, NMI presents as a critical regulator of epithelial-mesenchymal-plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…However, NMI was demonstrated to act as a downstream target of N‐myc and to be negatively related to cell growth in neuroblastoma (Wang, Gao, Wang, Xia, & Liang, ). NMI also has been reported to suppress tumor invasion and metastasis by inhibiting NF‐κB pathways in gastric cancer (Hou et al, ); NMI inhibited the growth of breast cancer through upregulating the expression of Dkk1 (Fillmore et al, ); downregulation of NMI promoted lung adenocarcinoma growth, which was correlated with the upregulated expression of COX‐2 (Wang et al, ); Nmi loss enhanced the mammary carcinoma metastasis in model mice (Pruitt et al, ). However, its function in the progression of CRC is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent findings show that N-Myc and STAT interactor (NMI) is expressed in the mammary ductal epithelium at the onset of puberty and is induced in pregnancy and lactation. NMI expression is critical for ensuring the maintenance of differentiated luminal epithelial cells 8 . Our mammary-specific NMI knockout mouse revealed that NMI loss disrupts luminal differentiation in the mammary glands affecting alveologenesis and prompts the progression of tumors with aggressive metastatic characteristics 8 .…”
Section: Introductionmentioning
confidence: 99%
“…NMI expression is critical for ensuring the maintenance of differentiated luminal epithelial cells 8 . Our mammary-specific NMI knockout mouse revealed that NMI loss disrupts luminal differentiation in the mammary glands affecting alveologenesis and prompts the progression of tumors with aggressive metastatic characteristics 8 . In agreement with this, NMI protein expression is significantly decreased in 70% of patient specimens with metastatic breast cancer compared to primary tumors 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%